Evaluación de cuatro fungicidas orgánicos para el control dela roya (Uromyces sppvulgaris L.) en el cultivo de la vainita (Phaseolus vulgaris L.). En el cantón Pimampiro provincia de Imbabura - Padilla Morales, Raúl Darwin (2013)
This research was conducted in the community of Chalguayacu , rural sector Pimampiro canton cantonal Imbabura province , geographically located at 0 ° 24 ' 0 " North Latitude and 77 ° 58 ' 0 " West Longitude , at an altitude of 2130 m in order to evaluate four organics to control rust ( Uromyces spp ) in growing vainita (Phaseolus vulgaris L.) . This study was conducted with the purpose of controlling one of the serious problems in this type of crop is by controlling rust Organic fungicides. Specific objectives evaluated the efficacy of organic fungicides on the incidence and severity of the fungus, the best treatment was determined organic fungicide to control rust and economically analyzed each of the treatments